Molecular Diversity of Candida albicans Isolated from Immuno-compromised Patients, Based on MLST Method - Seyed Mohammad Hosein AFSARIAN; Hamid BADALI; Tahereh SHOKOHI; Sohrab NAJAFIPOUR (Iranian Journal of Public Health, 2015)
Background: As regards multilocus sequence typing (MLST) method directly analyze the polymorphism within DNA sequences; we performed the first nationwide study on the genotypic relationships of Candida albicans strains obtained from oropharynx and bronchoalveolar lavage (BAL) samples from immunocompromised patients.